Greenwashing and Greenhushing in the Hungarian Consumer Market - Balku, Róbert; Fűrész, Ágnes; Kovács, Mátyás Imre; Szeberényi, András (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This study investigates the impact of greenwashing and greenhushing on consumer trust in the Hungarian market. Based on an online survey of 410 respondents conducted between November 1, 2024, and March 10, 2025, the results are presented through three research questions focusing on conceptual awareness, recall of international scandals, and purchasing decision factors. Data analysis utilized descriptive statistics and two-sample Z-tests at a 5% significance level. Findings reveal that while the Volkswagen “Dieselgate” scandal is widely recognized, other major cases – such as Chevron or BP – show a rapid decay in public memory. Furthermore, 74% of participants were completely unfamiliar with greenhushing. Statistical tests confirm that the inability to identify the „Seven Sins of Greenwashing” is a systemic issue, with over 34% of respondents unable to name a single deceptive practice. Due to “label fatigue”, consumers bypass official certifications, prioritizing social media and brand reputation.